Answers

2015-10-29T21:57:37+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
     1) -8+2 = x-3
Step One: Combine like terms.
   -8+2 = x-3
     -6   = x-3

Step Two: Transpose -3 to the left side. (Note: When you transpose, the sign must change.)
     -6   = x-3
 -6 + 3 = x

Step Three: Combine like terms.
  -6 + 3 = x
      -3   = x

The value of x is -3.

Checking:
   -8+2 = x-3
   -8+2 = (-3)-3
     -6   =  -6

     2) 5+x = 1/2-1/3
        5+x =   1/6
           x   = 1/6 - 5
           x   = -29/6 or -4.833...

     3) 1/4+x = 1/2-1/3
        1/4+x =   1/6
             x   = 1/6 - 1/4
             x   = -1/12 or -0.0833...
 
     4) 1-1/2+m = 3/4+1/2
          1/2+m   =    5/4
              m     = 5/4 - 1/2
              m     = 3/4
 
     5) (2/3)x = 4
           x    =  
                      2
                      3
            x    = 12/2
            x    =   6
 
     6) (1/5)y--7
        (1/5)y - (-7)
          1/5 y + 7
 
---Kein09---
1 1 1
  • Brainly User
2015-10-30T20:31:33+08:00
1)  -8 + 2 = x - 3
     -6 = x - 3
     x = - 6 + 3
     x = - 6

2)  5 + x = 1/2 - 1/3
     LCD: (2)(3) = 6
     (6)5 + (6)x = (6) 1/2 - (6) 1/3
      30 + 6x =  6/2 - 6/3
      30 + 6x = 3 - 2
       6x = 1 - 30
       6x/6 = -29/6
       x = -29/6

3)  1/4 + x = 1/2 - 1/3
    LCD of 4, 2, 3 is 12
    (12) (1/4) + (12)(x) = (12)(1/2) - (12)(1/3)
     3 + 12x = 6 - 4
     12x = 2 - 3
     12x/12 = -1/12
      x = -1/12

4)  1 - 1/2 + m = 3/4 + 1/2
     LCD of 2, 4  is 4
     (4)(1) - (4)(1/2) + (4)(m) = (4)(3/4) + (4)(1/2)
     4 -2 + 4m = 3 + 2
     2 + 4m = 5
     4m = 5-2
     4m = 3
     4m/4 = 3/4
     m = 3/4

5)  (2/3)x = 4
     (3/2)(2/3) x = 4(3/2)
     x = 12/3
     x = 6

6)  (1/5)y - - 7     (I hope you typed the given correctly)
     (1/5)y + 7
      
   If the given is (1/5)y = 7   (since this is Property of Equality)
   (1/5)y = 7
   (5/1)(1/5)y = 7(5/1)
   y = 35
0